2011
DOI: 10.1186/1550-2783-8-15
|View full text |Cite
|
Sign up to set email alerts
|

The effects of low and high glycemic index foods on exercise performance and beta-endorphin responses

Abstract: Τhe aim of this study was to examine the effects of the consumption of foods of various glycemic index values on performance, β-endorphin levels and substrate (fat and carbohydrate) utilization during prolonged exercise. Eight untrained healthy males underwent, in a randomized counterbalanced design, three experimental conditions under which they received carbohydrates (1.5 gr. kg-1 of body weight) of low glycemic index (LGI), high glycemic index (HGI) or placebo. Food was administered 30 min prior to exercise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 39 publications
0
25
0
3
Order By: Relevance
“…No significant difference observed in their work output performance among three meals but serum FFA were higher in LGI compare with HGI meal [17]. Despite, the controversial observations in individuals' exercise performance after low vs high GI meals, there was a relative shift in substrate utilization from carbohydrate to fat utilization, following low GI meals [16,21]. In our study RPE increased during the exercise period in both…”
Section: Discussionmentioning
confidence: 41%
See 3 more Smart Citations
“…No significant difference observed in their work output performance among three meals but serum FFA were higher in LGI compare with HGI meal [17]. Despite, the controversial observations in individuals' exercise performance after low vs high GI meals, there was a relative shift in substrate utilization from carbohydrate to fat utilization, following low GI meals [16,21]. In our study RPE increased during the exercise period in both…”
Section: Discussionmentioning
confidence: 41%
“…They observed that runners who consumed low versus HGI foods (30 vs 72), at 45 minutes priorto the exercise reflected a significant improvement in their 40-km performance [15]. Some of studies show no improvement in exercise performance after receiving LGI meals comparing with HGI meals [16][17][18]. Febbario et al studied receiving low or HGI meals on trained men (52 or 85) or even placebo (diet jelly) at 30 minutes before a cycling period, at 70% VO2max.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study was conducted on healthy subjects aged 18-44 years, because this age group is active and productive and has not yet undergone the changes in β-endorphin metabolism that occur in the elderly [9]. This study also limited the consumption of foods and medications that may affect β-endorphin levels [10,11]. Subjects with a BMI of 18.5-25 were part of the inclusion criteria to reduce the likelihood of metabolic differences that may affect β-endorphin levels [12,13].…”
Section: Discussionmentioning
confidence: 99%